Characterization of the complete chloroplast genome of Jilin ginseng (Panax ginseng C. A. Meyer) using next generation sequencing. Issue 2 (3rd July 2018) - Wang, Kangyu; Li, Li; Zhao, Mingzhu; Li, Shaokun; Sun, Honghua; Zhang, Meiping; Wang, Yi
Abstract: Jilin ginseng, Panax ginseng C. A. Meyer, belongs to the Araliaceae family. It is known as the number one medicinal herb and one of the three native treasures in Northern China and has been cultivated in China for over 2000 years. Jilin ginseng is the staple ginseng in China, which contributes to 85% of the ginseng production in the country, thus becoming one of the most important, rapidly increasing industries in both the Province of Jilin and China. In this study, the complete chloroplast genome of Panax ginseng C. A. Meyer was determined by the next generation sequencing. The complete chloroplast genome of Jilin ginseng ( P. ginseng C. A. Meyer) was 156, 286 bp in length and displays a typical quadripartite structure of the large (LSC, 87, 127 bp) and small (SSC, 18, 329 bp) single-copy regions, separated by a pair of inverted repeat regions (IRs, 25, 415 bp each). It harbors 132 functional genes, including 132 protein-coding genes, 37 transfer RNA, and 8 ribosomal RNA genes species. The overall nucleotide composition was: 30.6% A, 31.3% T, 19.4% C, and 18.7% G, with a total G + C content of 38.1%. Phylogenetic relationship analysis shows that P. ginseng closely related to Panax quinquefolius L.